2022
DOI: 10.1101/2022.08.09.503328
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Control of Motor Landing and Processivity by the CAP-Gly Domain in the KIF13B Tail

Abstract: Microtubules are a major component of the eukaryotic cytoskeleton that play crucial roles in diverse cellular process. Posttranslational modifications (PTMs) of tubulin dimers regulate the dynamics and organization of microtubules, as well as the interactions between microtubules and microtubule-associated proteins (MAPs). One unique PTM that occurs on microtubules is the cyclical removal and re-addition of the C-terminal tyrosine of α-tubulin. CAP-Gly (cytoskeleton-associated protein glycine-rich) domain cont… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…This would be because CC2 is not included in their assays. Indeed, the monomer-to-dimer conversion was observed upon release of the autoinhibition in the case of the full length of KIF13B which has the CC2 domain ( Fan and McKenney, 2022 ). The CC2 domain is conserved in most of the kinesin-3 family proteins including KIF1Bα, KIF1C, KIF13A, KIF16A, and KIF16B ( Hirokawa et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…This would be because CC2 is not included in their assays. Indeed, the monomer-to-dimer conversion was observed upon release of the autoinhibition in the case of the full length of KIF13B which has the CC2 domain ( Fan and McKenney, 2022 ). The CC2 domain is conserved in most of the kinesin-3 family proteins including KIF1Bα, KIF1C, KIF13A, KIF16A, and KIF16B ( Hirokawa et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…This would be because CC2 is not included in their assays. Indeed, the monomer to dimer conversion was observed upon release of the autoinhibition in the case of the full-length of KIF13B which has the CC2 domain (Fan, 2022). The CC2 domain is conserved in most of the kinesin-3 family proteins including KIF1Bα, KIF1C, KIF13A, KIF16A and KIF16B (Hirokawa et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, this would facilitate the formation of Kid dimers on the microtubules, leading to processive motility. These properties, such as 'the equilibrium between monomers and dimers' and 'the capability to exhibit processive movement on microtubules, even when characterized as monomers through mass photometry,' have been observed in kinesin-3 motors (28,31,32).…”
Section: Kid Is a Processive Motor Protein On Microtubulesmentioning
confidence: 92%
“…Recently, we and others have analyzed properties of full-length kinesins (26)(27)(28)(29). Notably, these studied have found that monomeric kinesins, including KIF1A, UNC-104 and KIF13B are converted to a dimer when activated (28,(30)(31)(32). For instance, in the autoinhibited and inactive state, KIF1A and UNC-104 are monomeric (30,32).…”
Section: Introductionmentioning
confidence: 99%